Mobile-health for recording and monitoring nutritional status of toddler during COVID-19 pandemic era - Hendryani, Atika; Nurdinawati, Vita; Susana, Ernia; Ma’murotun, Ma’murotun; Damayanti, Didit (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Indonesia has a large population in the world, and this is both an advantage and a challenge. The importance of recording and monitoring nutrition from the age of toddlers is a form of intervention to create a productive population. Integrated Healthcare Center or posyandu is community empowerment to monitor nutrition independently and sustainably. The pandemic caused by COVID-19 also affects the implementation of posyandu in Indonesia, one of which is in densely populated areas, namely Kelurahan Duri Selatan Jakarta Barat. This community service activity aims to apply mobile-health technology so that the nutrition monitoring activities of toddlers in posyandu continue to run during this pandemic. The technology used in this community service activity is a mobile-health application based on android, which is a form of application of technology from research. The method used is the provision of material online, then conducting assistance implementation practice. Evaluation of the results was achieved by applying pre-test and post-test to posyandu cadres and citizens. The evaluation results showed increased knowledge of posyandu cadres and residents after community service activities. This community service activity provides an alternative application of new technologies for community empowerment in improving nutritional status.